A Novel SSA Tuned PI-TDF Control Scheme for Mitigation of Frequency Excursions in Hybrid Power System. Issue 4 (1st October 2020) - Malik, Shilpam; Suhag, Sathans
ABSTRACT: In this work, a novel Salp Swarm Algorithm (SSA) tuned centralized hybrid proportional integral-tilt derivative with filter (PI-TDF) control scheme is proposed for mitigation of frequency excursions in hybrid power system (HPS) subjected to varying operating conditions due to variations of load and output powers of renewable energy systems (RESs). To bring out the eminence of SSA over other evolutionary algorithms implemented in this study, the comparative performance analysis is carried out. Further, frequency regulation performance of SSA tuned PI-TDF controller is compared against SSA tuned conventional PI/PID/TID/TIDF/P-TIDF controllers. The proposed control scheme is effective even with rate constraint non-linearity in the system; subsystems being switched on/off at different time instants; and with parametric changes introduced in one of the subsystems. The proposition, thus, is a viable and effective control scheme for frequency regulation in HPS while being robust and less sensitive. Graphical abstarct: uf0001